Beyond wilderness: towards an anthropology of infrastructure and the built environment in the Russian North*. Issue 1 (2nd January 2017) - Schweitzer, Peter; Povoroznyuk, Olga; Schiesser, Sigrid
Abstract: Public and academic discourses about the Polar regions typically focus on the so-called natural environment. While, these discourses and inquiries continue to be relevant, the current article asks the question how to conceptualize the on-going industrial and infrastructural build-up of the Arctic. Acknowledging that the "built environment" is not an invention of modernity, the article nevertheless focuses on large-scale infrastructural projects of the twentieth century, which marks a watershed of industrial and infrastructural development in the north. Given that the Soviet Union was at the vanguard of these developments, the focus will be on Soviet and Russian large-scale projects. We will be discussing two cases of transportation infrastructure, one of them based on an on-going research project being conducted by the authors along the Baikal–Amur Mainline (BAM) and the other focused on the so-called Northern Sea Route, the marine passage with a long history that has recently been regaining public and academic attention. The concluding section will argue for increased attention to the interactions between humans and the built environment, serving as a kind of programmatic call for more anthropological attention to infrastructure in the Russian north and other polar regions.